MicrobiomeStatPlots: Microbiome statistics plotting gallery for meta‐omics and bioinformatics - Bai, Defeng; Ma, Chuang; Xun, Jiani; Luo, Hao; Yang, Haifei; Lyu, Hujie; Zhu, Zhihao; Gai, Anran; Yousuf, Salsabeel; Peng, Kai; Xu, Shanshan; Gao, Yunyun; et al. (iMeta, 2025)
The rapid growth of microbiome research has generated an unprecedented amount of multi‐omics data, presenting challenges in data analysis and visualization. To address these issues, we present MicrobiomeStatPlots, a comprehensive platform offering streamlined, reproducible tools for microbiome data analysis and visualization. This platform integrates essential bioinformatics workflows with multi‐omics pipelines and provides 82 distinct visualization cases for interpreting microbiome datasets. By incorporating basic tutorials and advanced R‐based visualization strategies, MicrobiomeStatPlots enhances accessibility and usability for researchers. Users can customize plots, contribute to the platform's expansion, and access a wealth of bioinformatics knowledge freely on GitHub (https://github.com/YongxinLiu/MicrobiomeStatPlot). Future plans include extending support for metabolomics, viromics, and metatranscriptomics, along with seamless integration of visualization tools into omics workflows. MicrobiomeStatPlots bridges gaps in microbiome data analysis and visualization, paving the way for more efficient, impactful microbiome research. MicrobiomeStatPlots is a comprehensive platform for microbiome data analysis and visualization, offering bioinformatics tips, integrating multi‐omics pipelines, and featuring 82 visualization and interpretation cases. The platform allows users to customize the code and encourages contributions to expand its content, with plans for future updates. This platform is available at https://github.com/YongxinLiu/MicrobiomeStatPlot. Highlights Comprehensive visualization resources: MicrobiomeStatPlots provides over 80 reproducible visualization cases and integrates multi‐omics analysis pipelines to facilitate the analysis and interpretation of microbiome data. Customizable and user‐friendly: The platform includes detailed tutorials, example datasets, and R‐based plotting codes, enabling researchers to tailor visualizations to their needs. Collaborative and open‐source: MicrobiomeStatPlots encourages community contributions to expand its functionality and supports the continuous development of microbiome research. It's accessible for use and contribution at https://github.com/YongxinLiu/MicrobiomeStatPlot.